Bound State Solution of Dirac Equation for Generalized Pöschl-Teller plus Trigomometric Pöschl-Teller Non- Central Potential Using SUSY Quantum Mechanics - S. Suparmi; C. Cari (Journal of Mathematical and Fundamental Sciences, 2014)
The bound state solution of the Dirac equation for generalized Pöschl-Teller and trigonometric Pöschl-Teller non-central potentials was obtained usingSUSY quantum mechanics and the idea of shape invariance potential. Theapproximate relativistic energy spectrum was expressed in the closed form. Theradial and polar wave functions were obtained using raising and lowering ofradial and polar operators. The orbital quantum numbers were found from thepolar Dirac equation, which was solved using SUSY quantum mechanics and theidea of shape invariance.